STUDIES OF V.I. VERNADSKY ABOUT BIOSPHERE AND TRANSITION, BECOMING OF IT IN NOOSPHERE - Sova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The author analyses categories "biosphere" and "noosphere" of V.I. Vernadsky studies, exposes their maintenance. The way of transition of biosphere into noosphere is shown, the process of formation is given.